(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
The elderly are vulnerable people who need to be protected and protected due to their immense contributions to religion and the country. But today, urbanisation, career and education have made these people marginalised and neglected. Cases of abuse are also frequently displayed in the masses and print media as a result of the increasing population of Malaysian and world elders. This study aims to look at the protection of senior citizens in national legislation to examine the extent to which senior citizens’ rights are protected. The research is conducted using qualitative approach through the study of extinction and thermally analyzed. The results show that the existing legislation protects the rights of senior citizens in general but has not been comprehensive in meeting the rights of senior citizens. Therefore it is necessary for an amendment to the existing legislation or the drafting of legislation specifically for senior citizens to be done to meet the requirements. Keywords: Protection of senior citizens, rights of senior citizens, amendment of legislation, civil law, Islamic law, Malaysia Full text: PDF